MUTUAL FUND PERFORMANCE: SOME RECENT EVIDENCE FROM EUROPEAN EQUITY FUNDS - Božović, Miloš (Economic Annals, 2021)
This paper studies the performance of mutual funds that specialise in equity investment. We use a sample of the top sixteen actively managed European equity funds operating in the United States between July 1990 and November 2020. Using standard factor models, we show that none of our sample funds generated a positive and significant alpha. The observed funds could not outperform a simple passive strategy that involves tradeable European benchmark portfolios in the longer run. As a rule, the funds in our sample did not exploit the known asset pricing anomalies.